Continuous and noninvasive blood pressure measurement by pulse wave velocity : a new and systematic modeling methodology - Chen, Yan (2012)
Continuous and noninvasive blood pressure (BP) measurement has been a topic of study for years, and many commercial devices have been available. The most commonly used technologies (applanation tonometry and vascular unloading method) have a shortcoming of complex mechanical structure. In this thesis, a new and systematic methodology of continuous and noninvasive BP measurement by pulse wave velocity (PWV) is established for people with healthy cardiovascular system. To avoid complex and high-cost sensor or control system, arterial pulse waves are acquired using the easy-to-use, low-cost and technically mature photoplethysmography (PPG) sensors. Critical parts of this study include modeling BP-PWV relationship, determining two PWV's related to systolic blood pressure (SBP) and diastolic blood pressure (DBP) respectively, and verifying the modeling methodology by practical BP measurement using PWV. The measurement results from a small population satisfy the accuracy criteria of the Association for the Advancement of Medical Instrumentation (AAMI).